2013
DOI: 10.1186/1746-6148-9-168
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial on preweaning morbidity, growth and mortality in Holstein heifers fed a lacteal-derived colostrum replacer or pooled maternal colostrum

Abstract: BackgroundThe objective of this randomized controlled trial was to determine the effect of feeding a commercial lacteal-derived colostrum replacer (CR) or pooled maternal colostrum (MC) on preweaning morbidity, growth and mortality in Holstein heifer calves. A total of 568 calves were randomly assigned to be fed either 3.8 L of pooled MC or two doses (200 g IgG) of a CR. Calves were monitored daily for preweaning morbidity until weaning at 60 d old. Birth and weaning weights were measured to estimate growth ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
(47 reference statements)
1
7
0
4
Order By: Relevance
“…Colostrum replacement products have a highly variable performance [49,[58][59][60][61][62][63][64][65], and the herd veterinarian is advised to consult results of peer-reviewed controlled trials for separate products. Colostrum supplemented in milk replacer during the first 2 weeks of life (10 g IgG, bid) reduces NCD rates because of the intestinal activity of colostral antibodies and epithelial growth promoting substances [66].…”
Section: Colostrum Qualitymentioning
confidence: 99%
“…Colostrum replacement products have a highly variable performance [49,[58][59][60][61][62][63][64][65], and the herd veterinarian is advised to consult results of peer-reviewed controlled trials for separate products. Colostrum supplemented in milk replacer during the first 2 weeks of life (10 g IgG, bid) reduces NCD rates because of the intestinal activity of colostral antibodies and epithelial growth promoting substances [66].…”
Section: Colostrum Qualitymentioning
confidence: 99%
“…Similarly, colostrum-derived replacers with high doses of IgG (>170 g IgG) were shown to prevent FPT; however, some but not all colostrum-derived replacers and supplements with lower doses of IgG also prevented FPT [ 8 , 12 , 25 , 27 – 31 ]. Studies of plasma-derived replacers have shown either no difference or an increased risk of health events in calves compared to colostrum, whereas studies of colostrum-derived replacers have shown both a decreased and increased risk of health events in calves compared to colostrum [ 23 , 25 , 26 , 32 ]. Feeding pooled colostrum in conjunction with a CDR has not been evaluated and could be an effective approach to address colostrum shortages on dairies.…”
Section: Introductionmentioning
confidence: 99%
“…Una falla en la TIP se ha correlacionado con una mayor incidencia de enfermedades, mayor mortalidad, mayor edad para alcanzar el peso a servicio y un potencial menor producción de leche durante la primera lactancia (DeNise et al, 1989;Furman-Fratczak et al, 2011;Aly et al, 2013).…”
Section: Introductionunclassified
“…Con respecto al estado de salud de los animales, hay estudios que reportan una asociación entre la concentración sérica de IgG y la incidencia de enfermedades. Se ha visto una menor incidencia de diarreas cuando se alimentó un sustituto de calostro (Aly et al, 2013); sin embargo, Priestley et al (2013) indicaron que alimentar con sustituto de calostro resultó en una morbilidad mayor.…”
Section: Introductionunclassified
See 1 more Smart Citation